Lagenorhynchus australis Peale 1848 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lagenorhynchus australis Peale 1848 Lagenorhynchus australis Peale 1848, Mammalia, in: Repts. U. S. Expl. Surv., Vol. 8: 33. Type Locality: "South Atlantic Ocean, off the coast of Patagonia", Argentina, 1 day’s sail north of the Straits of LeMaire. Vernacular Names: Peale's Dolphin. Synonyms: Lagenorhynchus amblodon (Cope 1866); Lagenorhynchus chilensis (Philippi 1896). Distribution: Chile to Argentina: Valparaiso to Commodoro Rivadavia and Falkland Isls: Cold-temperate waters. One published (photograph) sighting in the tropical waters of the South Pacific, Cook Isls (Leatherwood et al., 1991). Conservation: CITES – Appendix II; IUCN – Data Deficient. Discussion: Included in cruciger by Bierman and Slijper (1947) and Hershkovitz (1966 a :67), but considered a distinct species by Fraser (1966), Rice (1977), Brownell (1974), and Mitchell (1975 a ). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 729, DOI: 10.5281/zenodo.7316519